The effectiveness of e-Government services: a study on the e-Procurement system at the Ministry of Health (MOH) / Suhaida Mohd Kamirazaman - Mohd Kamirazaman, Suhaida (2019)
E-Government or electronic government is one of the categories in Information and Communication Technology (ICT) that widely used in many developing and developed countries as it provides great benefits to the Government in improving the quality of service to the people. e-Procurement is one of the e-Government services used by the Malaysian Government as a tool for the public procurement process. However, the effectiveness of the system is perceived below the target with more issues arise. Therefore, the purpose of this study is to determine the effectiveness of the e-Procurement system in public procurement. Besides, the study also aims to examine the relationship between the effectiveness of e-Procurement with the factors of accessibility, compatibility, user's attitude, and transparency of the system. This study has applied two related theories or models, namely the Success Model for Malaysian Government e-Procurement System and the Actual Used Model of Malaysia's e-Government System. The scope of the study was focused on the users of the e-Procurement system in the Ministry of Health, which involves government servants and suppliers. The study was conducted through quantitative research methods using a survey questionnaire. The findings of this study indicate that e- Procurement system was effective and give many benefits to the government and suppliers. In addition, factors of accessibility, compatibility, user's attitude, and transparency have significant implications and impact on the effectiveness of the e-Procurement system. Significant correlations have also been obtained, which indicate that there is a positive relationship between the effectiveness of the e-Procurement system and all the factors. The study also revealed that user's attitude becomes the main factor that influences the effectiveness of e-Procurement system. Therefore, several recommendations have been outlined and proposed for enhancement of the system which requires commitment from all parties, including government, vendor, users and suppliers. Future researchers are recommended to implement mix research methods and expand the scope of the study to increase data collection and enhance the accuracy of the study results.